Effects on EMG Response of Lower limb and Heart Rate of walking in the water on Different Water Depth* - Kim, Ki-Hong; Jeong, Hwan-Jong; Koo, Geun-Hwe; Yang, Chun-Ho (International Journal of Engineering and Technology, 2019)
Background/Objectives:This studywas investigate changes in muscle activity and heart rate of the lower extremities when walking according to the depth of water in 20 years old male. The subjects of this study are seven male men who are healthy in their 20s and live in C city in Chungnam and who signed voluntary agreements. The subjects would be provided with sufficient preliminary explanations about the purpose of this study and the experimental procedures in advance so that they can give up their participation according to their own would.Methods/Statistical analysis:To measure the subject's muscle activity, This study did use a surface wire EMG (Laxtha: Korea) and measure the EMG response before and after each experiment in an isometric squat posture. I would perform an isometric squat with a knee bent 90 degrees and would measure the iEMG value for 5 seconds.Findings:Knee depth Walking in the Water increases the iEMG of the lower limb, and Walking in the Water in the waist deep reduces the iEMG. In addition, heart rate showed a greater increase in waist depth than Walking in the Water.Improvements/Applications:Walking in the Water in the waist height is effective for recovery the muscle fatigue of the Lower LimbÂ Â